ROLE OF LEPAKALPANA FOR IMPROVING BEAUTY OF SKIN W. S. R. TO MUKHALEPA - Chaudhari, *Tejaswini Govind; Sneha, Kubde; Mukund, Dive; Pallavi, Jamnekar (International Journal of Ayurveda and Pharma Research, 2017)
Skin (Twacha) is the largest organ of the body and has a great cosmetic value. It is one of the five Jnanendriyas (sense organs) i.e., Sparsha jnyaan (touch sensation) gets from it. So it has ample of importance in physical and mental well being of an individual. It is most vulnerable to disease as it exposes to external environment. There are lots of reasons behind the skin problems and most striking is the todays busy and stressful life. Skin disorders affects all ages from the neonates to the elderly persons. Ayurveda an ancient science has vast description of the topical applications in the name of Lepa kalpana described both as the Chikitsa (treatment) of various skin diseases and for beauty. The medicines that are in the form of a paste and used for external application are called as Lepas. A great demand from Ayurveda in the field of cosmetology has been established due to its unique concept about beauty and effective, cheaper and long lasting therapy without any side effects. The herbal paste which is applied on face to treat acne, pimples, scars, marks and pigments are known as Mukha Lepa (face pack) in Ayurveda. Mukhalepa is a simple and effective skin care treatment in Ayurveda, which is done using variety of herbal pastes. The herbal face pack mainly consists of different rejuvenating herbs that help in nourishment of the skin and also aid in skin cleansing and make it soft and clear. Mukhalepas also helps to increase the elasticity of the skin and thereby prevents the ageing of the skin, avoids wrinkles on the face, and gives a good skin tone. The present article is aimed to provide the details about the Lepa kalpana from the classics of Ayurveda, the concept of Mukha lepa and the drugs mentioned in classics which are useful for improving complexion and for the common skin ailments.